1999
DOI: 10.1203/00006450-199911000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Correlations in Phenylketonuria: Mutation Patterns and Corresponding Biochemical and Clinical Phenotypes in a Heterogeneous California Population

Abstract: We studied 133 California phenylketonuria (PKU) patients and one obligate heterozygote to delineate the molecular basis of PKU in a population with greater ethnic diversity than in previous studies, and to determine whether a correlation exists between genotype and clinical phenotype, with the latter defined by both the diagnostic pretreatment blood phenylalanine (PHE) level and cognitive (IQ) test scores. To determine PAH genotypes, we used PCR-mediated amplification, denaturing gradient gel electrophoresis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
3
6
0
1
Order By: Relevance
“…Homozygosity rate in Rio de Janeiro PKU population revealed a high genetic heterogeneity (j = 0.063), similar to that found in South Portugal (0.059) (Rivera et al, 2011), Galicia (0.054) (Couce et al, 2013), USA (nationwide index of 0.06) (Guldberg et al, 1996), and in California for the European descent subgroup (0.06) (Enns et al, 1999). Nevertheless, considering that the higher the value of j, the more homogeneous the population with respect to the PAH locus, our population was more homogeneous than the PKU population of Spain (0.029) (Aldamiz- Echevarria et al, 2016), and the Hispanic population of California (0.04) (Enns et al, 1999).…”
Section: Mutational Spectrumsupporting
confidence: 72%
“…Homozygosity rate in Rio de Janeiro PKU population revealed a high genetic heterogeneity (j = 0.063), similar to that found in South Portugal (0.059) (Rivera et al, 2011), Galicia (0.054) (Couce et al, 2013), USA (nationwide index of 0.06) (Guldberg et al, 1996), and in California for the European descent subgroup (0.06) (Enns et al, 1999). Nevertheless, considering that the higher the value of j, the more homogeneous the population with respect to the PAH locus, our population was more homogeneous than the PKU population of Spain (0.029) (Aldamiz- Echevarria et al, 2016), and the Hispanic population of California (0.04) (Enns et al, 1999).…”
Section: Mutational Spectrumsupporting
confidence: 72%
“…We found a moderate correlation between predicted PRA and the inverse of pretreatment Phe levels (r = 0.456, n = 80). Earlier work, summarized by Enns et al (1999), also found this correlation. But those authors themselves did not corroborate it.…”
Section: Discussionsupporting
confidence: 62%
“…Earlier work, summarized by Enns et al. (), also found this correlation. But those authors themselves did not corroborate it.…”
Section: Discussionsupporting
confidence: 62%
“…O fenótipo bioquímico, estabelecido pela dosagem de Fal ao diagnóstico, nos permite inferir a atividade enzimática residual e, portanto, a resposta à dietoterapia. Entretanto, tal correlação necessita do suporte do conhecimento das mutações causadoras de doença em cada caso, [16][17][18] estudo esse já em andamento neste mesmo Serviço, em parceria com a FIOCRUZ da Bahia.…”
Section: Discussionunclassified